2019
DOI: 10.1167/iovs.18-26234
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Decline of Retinal Oxygen Extraction in Healthy Subjects

Abstract: PURPOSE. To investigate the age-dependence of total retinal blood flow and total retinal oxygen extraction in healthy subjects and determine their possible correlations with structural optical coherence tomography (OCT) parameters. METHODS. This observational cross-sectional study consisted of 68 healthy subjects (mean 6 SD age, 45.6 6 16.3 years; 47% female). Total retinal oxygen extraction was calculated based on measurement of total retinal blood flow using bi-directional Doppler OCT and measurement of oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 62 publications
(74 reference statements)
3
26
0
Order By: Relevance
“…Previous studies have indicated an age-related decline in retinal blood flow. 32,48,49 In this study we did, however, include only healthy young subjects, and the age range was narrow. Whereas some studies indicate higher retinal blood flow in women, 50 data are controversial, and no clear evidence for gender differences exists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated an age-related decline in retinal blood flow. 32,48,49 In this study we did, however, include only healthy young subjects, and the age range was narrow. Whereas some studies indicate higher retinal blood flow in women, 50 data are controversial, and no clear evidence for gender differences exists.…”
Section: Discussionmentioning
confidence: 99%
“… 46 We have previously presented a method for calculating total retinal oxygen extraction by coupling the dual-beam Doppler OCT system to a fundus camera. 7 , 31 , 32 Although we have not explicitly studied the repeatability and reproducibility of this approach, it can be estimated based on our previous results on the variability of oxygen saturation measurements 47 and the data obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simultaneous measurement of oxygen saturation in a pair of retinal artery and vein can assess the arteriovenous difference of oxygen saturation and oxygen content, CaO 2 -CvO 2 (See Equation (1)). The latter provides information on the retinal oxygen consumption in the tissue supplied by the artery and drained by the vein, an important parameter, which is related to the metabolism rate of the retinal cells [ 78 , 79 ]. The arteriovenous difference of oxygen saturation or oxygen content decreased during breathing of 100% oxygen relative to breathing air in measurements on healthy subjects [ 78 , 80 ], but was unchanged in COPD patients [ 75 ].…”
Section: Pulse Oximetry—theory and Techniquesmentioning
confidence: 99%
“…Non-invasive retinal oximetry has been used in physiological studies on healthy persons [ 68 , 70 , 74 , 78 , 79 , 80 ] and on patients with ophthalmic and a number of systemic diseases [ 70 , 75 , 81 , 82 , 83 , 84 , 85 , 86 ]. The increase in arteriovenous difference of retinal oxygen saturation is generally due to ischemia, while the decrease in that difference might originate from atrophy, which is associated with lower metabolism of retinal cells.…”
Section: Pulse Oximetry—theory and Techniquesmentioning
confidence: 99%